Internalisasi Kearifan Lokal dalam Pembelajaran Seni Budaya dan Prakarya (SBDP) untuk Menanamkan Literasi Budaya Siswa Madrasah Ibtidaiyah - lestari, Sri; Dina Hafni, Nurlaili (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Internalization of Local Wisdom in SBDP Learning to Foster Cultural Literacy of Fourth Grade Students at MI Sumbersari Kowang Tuban in the 2025/2026 Academic Year is motivated by students’ limited understanding and appreciation of local culture amid globalization. This study aims to describe the forms of local wisdom values integrated into learning, the internalization process in Arts, Culture, and Craft learning, and its impact on students’ cultural literacy. This research employed a descriptive qualitative approach involving one teacher and 36 fourth grade students of MI Sumbersari Kowang Tuban. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the values of hard work, mutual cooperation, responsibility, and environmental awareness embedded in the traditions of legen and siwalan can be contextually integrated into classroom activities. The internalization process occurred through stages of understanding, reflection, and creative practice. The implementation of local wisdom-based learning significantly improved students’ cultural understanding, appreciative attitudes, and cultural expression. Therefore, integrating local wisdom into Arts, Culture, and Craft learning effectively strengthens cultural literacy among elementary school students.